A Flexible Framework Integrating Digital and Social Competences in Vocational Education Across Diverse Contexts - María José Hernández-Serrano; Joe Cullen; Barbara Jones; Noelia Morales Romo (Media and Communication)
Competence frameworks in general education environments have emerged to define the knowledge, skills, and attitudes that contemporary educators need to acquire. Such frameworks have been less developed within vocational education and training (VET) although this sector is directly impacted by rapid and complex technological changes increasingly embedded in industrial and organisational demands of the working context. Many VET classrooms with dual or flexible contexts, with a range of demographically and culturally diverse learners, now require teachers to be trained with new competences and cross-cutting skills to cope with the resultant wider and deeper changes in knowledge. This article presents the outcomes and data of the design and validation processes of a competence framework combining digital and social skills. It was piloted in five countries (UK, Sweden, Germany, Italy, and Spain) to provide a flexible, and needs-based competence framework for VET teachers working with vulnerable learners. After conducting a literature review and a needs assessment of VET teachers and learners, a flexible three-domain framework is presented, with pathways and training methods that account for the so-called poly-contextual skills that combine digital and social skills. The flexible framework and 26 competences were tested with 358 VET teachers using three evaluation tools (self-assessment survey, game-quiz scores, and programme satisfaction survey). Conclusions highlight the need to combine digital and social skills together with media literacy through flexible pathways to achieve better results for teaching, learning, and empowering learners.